Variation of Stem Radius in Response to Defoliation in Boreal Conifers - Balducci, Lorena; Rozenberg, Philippe; Deslauriers, Annie (Frontiers in Forests and Global Change, 2021)
In the long term, defoliation strongly decreases tree growth and survival. Insect outbreaks are a typical cause of severe defoliation. Eastern spruce budworm outbreaks are one of the most significant disturbances of Picea and Abies boreal forests. Nevertheless, in boreal conifers, a two-year defoliation has been shown to quickly improve tree water status, protect the foliage and decrease growth loss. It suggests that defoliation effects are time-dependent and could switch from favorable in the short term to unfavorable when defoliation duration exceeds 5 to 10 years. A better understanding of the effect of defoliation on stem radius variation during the needle flushing time-window could help to elucidate the relationships between water use and tree growth during an outbreak in the medium term. This study aims to assess the effects of eastern spruce budworm (Choristoneura fumiferana Clem.) defoliation and bud phenology on stem radius variation in black spruce (Picea mariana (Mill.) B.S.P.) and balsam fir (Abies balsamea Mill.) in a natural stand in Quebec, Canada. We monitored host and insect phenology, new shoot defoliation, seasonal stem radius variation and daytime radius phases (contraction and expansion) from 2016 to 2019. We found that defoliation significantly increased stem growth at the beginning of needle flushing. Needles flushing influenced the amplitude and duration of daily stem expansion and contraction, except the amplitude of stem contraction. Over the whole growing season, defoliation increased the duration of stem contraction, which in turn decreased the duration of stem expansion. Our results reveal that defoliation promotes a greater stem growth at the beginning of needles flushing. However, the change (increase/decrease) of the duration of contraction/expansion reflects a progressive decline of the potential recovery from defoliation. Black spruce showed significantly larger 24-h cycles of stem amplitude compared to balsam fir. However, both species showed similar physiological adjustments during mild stress, preventing water loss from stem storage zones to support the remaining needles’ transpiration. Finally, conifers react to defoliation during a 4-year period, modulating stem radius variation phases according to the severity of the defoliation.